Quality of Life in Thalassemia Major Patients: Reliability and Validity of Indonesian Version of TranQol Questionnaire - Billy Ng Setiawan Rachmat Poengoet; Ellyana Sungkar; Tri Damiati Pandji (International Journal of Integrated Health Sciences, 2017)
Objective: To determine the validity and reliability of TranQol questionnaire that has been translated into Indonesian to be used in Indonesian thalassemia major patients. The quality of life problems among these patients can be detected earlier because TranQol is more precise compared to the Pediatric Quality of Life Inventory (PedsQLTM), World Health Organization Quality of Life Instruments (WHOQOL), and SF-36 Questionaire.Methods: This study was conducted in Bandung, Indonesia from October 2015 to March 2016 and used a standard “forward-backward” translation procedure. It involved 60 adults and 73 children who are thalassemia major patients, and 71 parents of patients in Dr. Hasan Sadikin General Hospital. TranQol was processed through forward and backward translation approach and evaluation was conducted by the TranQol author. After the translation process, a cognitive debriefing was performed and the translated TranQol was tested to all subjects.Results: Cronbach’s alpha >0.7 was used for all TranQol categories. Front validity and content validity testing was performed. The internal validity results showed that some questions were not valid.Conclusions: TranQol reliability in Indonesian language for every category is good. Validity for TranQol in Indonesian language shows that the translated TranQol is not quite suitable that it still cannot be used. Keywords: TranQol Indonesia, validity Indonesia, reliability Indonesia DOI: 10.15850/ijihs.v5n2.1011